A musicall banquet of daintie conceits Anthony Munday's 1588 miscellany with tunes - Munday, Anthony 1553-1633 (A-R Editions, Inc., 2023)
"In 1588 Anthony Munday published A Banquet of Daintie Conceits, containing twenty-two new moral poems in various verse forms. Ranked with the best comic playwrights of his day, including Shakespeare, he was also a travel-writer, religious spy, actor, translator, royal messenger, deviser of civic entertainments, and historian. Munday confessed that he was not knowledgeable in music, yet he named a tune for singing each poem. Intriguingly, unlike typical broadside ballad tunes, most of Munday's tunes are dances, and of the twenty-two named, fourteen are known from solo instrumental arrangements. Despite that survival, despite the poet's fame, and despite an 1812 edition of the poems from the unique extant copy, this is the first attempt to set Munday's Banquet lyrics to their respective music. Poems with unidentified melodies are set to period tunes that fit their versifications, making all the lyrics singable for the first time in over 400 years"--
Songs with continuo
Unfigured bass not realized
Keywords: Songs (Medium voice) with continuo; English poetry / 16th century / Musical settings; English poetry; 1500-1599; Musical settings; Poetry; Scores; Songs; Chamber music